Implementasi Motor Servo SG 90 Sebagai Penggerak Mekanik Pada E. I. Helper (ELECTRONICS INTEGRATION HELMET WIPER) - Akhmad Irfansyah Salim; Yuliarman Saragih; Rahmat Hidayat (Electro Luceat, 2020)
Many motorcyclists face problems when it rains, visibility limited helmet glass when driving can be one of the factors that cause it traffic accidents. Wiper Helm or E. I. Helper is a tool for motorcyclists which has a function to clean the helmet glass from a limited visibility when it rains down, by adjusting the measurement angle calculation 00-1100, with the average duration delay time 3.35 seconds to clean the helmet glass back and forth, the experiment was carried out 9 times on the helmet glass with a stable testing success rate. In the E. I. Helper mechanical movement system that has been installed to program data through the Arduino IDE application, the SG 90 Servo Motor mechanical drive system is used and the Arduino Nano Atmega 328 microcontroller. Mechanical motor Servo SG 90 on the circuit E. I. Helper will have an active status of electric power flowing with a push button switch while ON condition The E. I. Helper circuit will have an inactive status when the push button switch is OFF.